Productivity and Quality of Three Varieties of Ginger on Many Light Intensity Levels Under Stand of Pine - Gunawan - Gunawan; Asep Rohandi (Jurnal Agroforestri Indonesia, 2018)
The high demand of medicinal plants with limited agricultural land availability can be solved by the utilization of land under forest canopy through applying agroforestry. This study aims to assess the effect of different varieties of ginger and different shading intensities of pine (Pinus merkusii) on the productivity and quality of ginger. The design used was a split plot design consisting of 3 replicates with an area of  100 m2 for each plot and with spacing of 50 x 50 cm. The main plot is the light intensity treatments, i.e. 50-58% (age class II), 68-77% (age class I) and 87-92% (poor increment), whereas the sub plot is the varieties of ginger i.e.: small white ginger (emprit), large white ginger (gajah) and red ginger. Results showed that the light intensity does not significantly affect the percentage of growth, moisture content, volatile oil, fiber, starch and ash. Varieties of ginger significantly affect the percentage of growth, height growth and weight of rhizome, but do not significantly affect the moisture content, volatile oil, fiber, starch and ash . The average yield of each variety of ginger is 5.54 tons/ha, 8.38 tons/ha and 6.7 ton /ha for small white ginger, large white ginger and red ginger, respectively. Agroforestry of ginger plant under pine stand can be done to improve land productivity, especially in poor stand increment.